2018
DOI: 10.1111/bjh.15642
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors affecting outcome of unrelated cord blood transplantation for children with familial haemophagocytic lymphohistiocytosis

Abstract: Allogeneic haematopoietic stem cell transplantation is still the only available curative option for Familial Haemophagocytic Lymphohistiocytosis (FHLH). Most studies report outcomes after bone marrow or peripheral blood stem cell transplantation. We analysed the outcomes of 118 children with FHLH undergoing single-unit umbilical cord blood transplantation performed from 1996 to 2014. Myeloablative conditioning regimen was given to 90% of the patients, and was mostly busulfan-based (n = 81, 76%), including anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In a small cohort of only 12 patients receiving unrelated cord blood transplantation and variable reduced intensitiy conditioning regimen, full chimerism could be achieved in most patients with familial hemophagocytic lymphohistiocytosis (FHL). 7 Serotherapy is likely to be a crucial factor regarding mixed chimerism. Alemtuzumab has been widely used in HLH conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a small cohort of only 12 patients receiving unrelated cord blood transplantation and variable reduced intensitiy conditioning regimen, full chimerism could be achieved in most patients with familial hemophagocytic lymphohistiocytosis (FHL). 7 Serotherapy is likely to be a crucial factor regarding mixed chimerism. Alemtuzumab has been widely used in HLH conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with most publications, 4,31 while this effect could not be shown in a cohort of unrelated cord blood transplantations in HLH. 7 In summary, the appearance of substantial recipient chimerism remains a major challenge in HSCT of HLH (when using reduced toxicity regimes). We demonstrated that an HLA-mismatched donor is an independent risk factor and confirmed that active disease at start of conditioning is a poor prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative donors should therefore be considered early. Unrelated umbilical cord blood transplantation may provide a readily available alternative donor source, and 6-year overall survival of 55% has been reported in a recent analysis of 118 patients receiving mostly busulfan-based conditioning (32).…”
Section: Alternative Donorsmentioning
confidence: 99%
“…Finally, for familial haemophagocytic lymphohistiocytosis (HLH), although the best results are obtained with MSD transplantation, unrelated UCB can be used as a source of HSC, with OS from 55% to 76% (Table D). A recent study by Eurocord reported an OS of 55% in children with familial HLH transplanted from unrelated UCB, with best results with higher cell dose (OS 65% with TNC >9.9 10 7 /kg) and better HLA match (DFS 69% with 6/6 HLA‐match) (Furtado‐Silva et al , ). A smaller Japanese study, moreover, showed that UCBT may be feasible even after RIC in HLH patients with established organ dysfunction (Sawada et al , ).…”
Section: Cord Blood Transplantation In Primary Immunodeficiency Syndrmentioning
confidence: 99%